Influence of Smartphone Overuse on Grip Strength, Pinch Strength, and Cross-Sectional Area of Flexor Pollicis Longus Tendon and Median Nerve - Samuel, Paul Silvian; Alahmari, Khalid A; Adam, Mohamed; Reddy, Ravi Shankar; Ahmad, Irshad; Kakaraparthi, Venkata Nagaraj; Rengaramanujam, Kanagaraj; Tedla, Jaya Shanker; Hussein, Almohiy; Alshahrani, Mastour Saeed (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2021)
Background and Aim The adverse effects of smartphone size and weight on the hand and hand function have not been studied extensively. This study aimed to investigate the changes to the flexor pollicis longus tendon and median nerve using diagnostic ultrasound for high and low addiction smartphone users.Methodology In this cross-sectional study, 54 healthy male university students were divided into two groups according to the Smartphone Addiction Scale: high and low users. Demographic data, hand grip strength (kg), pinch strength (kg), and smartphone weight, length and width were measured and recorded. Diagnostic ultrasound examination determined the cross-sectional area of the median nerve (mm2) and flexor pollicis longus tendon (mm2) of the dominant and non-dominant hand.Result The cross-sectional area of the median nerve was significantly higher in the high-user group (7.4±1.3 mm2) than the low-user group (6.7±1.0 mm2). The correlation of phone weight, length and width with median nerve area was respectively positive, higher and significant (0.718, 0.747, and 0.733; p<0.05). The flexor pollicis longus tendon in the mid-thenar region was moderately positively correlated with phone length (0.430; p<0.02) for high addiction smartphone users.Conclusion The findings of the current study demonstrates that change to the median nerve and flexor pollicis longus tendon, could be linked to the width, weight and length of the smartphone and high addiction.
Keywords: Smartphone; Addiction; Flexor Pollicis Longus Tendon; Median Nerve; Ultrasound.